Alteraciones psicológicas en niños y adolescentes como consecuencia de la migración de los padres - Oleas Alava, Ana Juliette (2024)
Childhood and adolescence are critical periods in human development, so the presence of parents largely determines psychological well-being, which significantly influences the achievement of personal and professional success. The objective of this study was to determine the psychological alterations presented by children and teenagers as a consequence of parental migration. The research is a documentary bibliographic research with a descriptive level. The study was initially made up of 130 scientific articles from different databases of worldwide impact such as PubMed, Springer Link, Medigraphic, Scopus, Multidisciplinary Digital Publishing Institute (MDPI), Google Scholar and Frontiers. These scientific articles were written in Spanish and English, during the period between 2014 and 2024. After applying specific selection criteria, employing Boolean operators and relevant keywords, as well as using search algorithms for information filtering, and carrying out a rigorous evaluation of the methodological quality of the documents, the research was finally constituted of 46 scientific articles relevant to the study variables. The literature review technique was used, using the literature review form and the Critical Review Form-Quantitative Studies (CRF-QS) as instruments to evaluate the methodological quality of the selected articles. Among the results, it was found that children of migrant parents face various psychological alterations, such as anxiety, depression, behavioral problems (hyperactivity, inattention), difficulties in socioemotional development and in interaction with their peers. On the other hand, adolescents show behavioral problems such as hyperactivity, difficulties with their peers, low prosocial behavior, somatic symptoms and traits associated with personality disorders. At the emotional level, depression, suicidal ideation, anxiety, low self-esteem, stress, emotional instability and poor interpersonal sensitivity were observed, in addition to learning and adaptation problems. In conclusion, parental presence is essential for the integral wellbeing of children and adolescents because it provides an emotionally secure environment that promotes self-esteem and social skills, in addition to stimulating learning and the development of academic skills.